EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN VISUALIZATION AUDITORY KINESTIC (VAK) TERHADAP KEMAMPUAN PEMECAHAN MASALAH TEMATIS SISWA DI KELAS XI SMA NEGERI 1 SIBABANGUN - Gurgur Rodop Mauli; Nunik Ardiana; Roslian Lubis (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
The aim of this study was to know whether effective using VAK learning model on students’ mathematical problem solving ability on the topic of sequence and series at the eleventh grade students of SMA Negeri 1 Sibabangun. The research was conducted by applying experimental method (one group pretest post test design) with 34 students as the sample and they were taken by using cluster random sampling technique from 198 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using VAK learning model was 3.8 (very good category) and (b) the students’ mathematical problem solving ability on the topic of sequence and series before using VAK learning model was 52.5 (fair category) and after using VAK learning model was 84.11 (very good category). Furthermore, based on inferential statistic by using pair sample ttest, (SPSS version 22), the result showed the significant value was less than 0.05 (0.000<0.05) and by using N- gain formulation showed 0.67 (effective category). It means, using VAK learning model was effective used on students’ mathematical problem solving ability on the topic of sequence and series at the eleventh grade students of SMA Negeri 1 Sibabangun.